PENGARUH JARAK TANAM DAN HASIL TANAMAN KACANG TANAH (Arachis hypogea L ) PADA TUMPANG SARI TANAMAN JERUK DI DESA KEPPO KECAMATAN GALIS - Lia Kristiana; Marchel Putra Garfansa; Maulidi Ahmad (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
This study aims to find out the influence of planting distance on the growth and yield of peanut crops and optimal planting distances that can increase peanut growth. This research was conducted in Keppo Village of Pamekasan District Galis District November 2021 - January 2022. The research design uses a RandomIzed Group Design (RAK) which consists of 5 types of planting systems with 4 repeats so that there are 20 plots of treatment. Data that has been obtained using diversity analysis (ujiF) with a 5%. If you get a real influence, then continue to use BNT (Small Difference) with a 5% The results showed that the influence of the planting distance of peanuts that are superimposed with citrus plants has a noticeable influence on variable number of pods, weight of land pods, weight of 100 pods and crop yield perhektar. The most optimal peanut planting distance of all treatments is JT 3 (40 x 20 cm).